Motivation and Justice at Work: The Role of Emotion and Cognition Components of Personal and Collective Work Identity - Nordhall, Ola; Knez, Igor (Frontiers in Psychology, 2018)
The aim of this study was to investigate the role of personal and collective work identity (including emotion and cognition components), in predicting work motivation (operationalized as work self-determined motivation) and organizational justice (operationalized as organizational pay justice). Digitized questionnaires were distributed by e-mail to 2905 members, teachers, of a Swedish trade union. A total of 768 individuals answered the questionnaire and by that participated in this study. Personal- compared to collective work identity was shown to positively associate with self-determined motivation accounted for by the emotion component of personal work identity. Collective compared to personal work identity was reported to positively associate with organizational pay justice accounted for by the cognition component of collective work identity. All this suggests that both work-related motivation and organizational justice might be, to some extent, accounted for by the psychological mechanisms of work identity and that, as predicted, different types of work identity, play different significant roles in predicting motivation and justice at work. More precisely, the emotion component of work identity was more pronounced in personal work-bonding relationships, and the cognitive component, of work identity in contrast, was more pronounced in collective work-bonding relationships.